2017
DOI: 10.1038/s41598-017-00711-w
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the structure and distribution changes of Eucalyptus lignin during the hydrothermal and alkaline pretreatments

Abstract: An integrated pretreatment process based on hydrothermal pretreatment (HTP) followed by alkaline pretreatment has been applied to treat Eucalyptus. The chemical composition and structure changes of lignin during the pretreatment were comprehensively characterized. The surface morphology of the cell walls and lignin distribution of the pretreated Eucalyptus were detected by scanning electron and confocal Raman microscopies. It was found that the chemical bonds between lignin and hemicelluloses were cleaved duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 45 publications
3
45
0
1
Order By: Relevance
“…This may be due to the hydrolysis of lignin being greatly dependent on access to the alkali solution; therefore, high accessibility between the epidermis and alkali solution lead to a significant degradation of lignin, as well as to less lignin degradation in the middle of cross sections along with less accessibility to the alkali solution. This result was consistent with former research [59], in which the lignin distribution change in fiber cells of Eucalyptus was illustrated by Raman images with the integration of band intensity (1547-1707 cm −1 ), however, with the exception of fiber cells, other types of cells had not been studied. Furthermore, a distribution change of polysaccharides, the core components of lignocellulosic biomass transformation, had also not been studied [59].…”
Section: Chemical Imaging Of Untreated and Alkali-treated Rice Straw supporting
confidence: 93%
See 1 more Smart Citation
“…This may be due to the hydrolysis of lignin being greatly dependent on access to the alkali solution; therefore, high accessibility between the epidermis and alkali solution lead to a significant degradation of lignin, as well as to less lignin degradation in the middle of cross sections along with less accessibility to the alkali solution. This result was consistent with former research [59], in which the lignin distribution change in fiber cells of Eucalyptus was illustrated by Raman images with the integration of band intensity (1547-1707 cm −1 ), however, with the exception of fiber cells, other types of cells had not been studied. Furthermore, a distribution change of polysaccharides, the core components of lignocellulosic biomass transformation, had also not been studied [59].…”
Section: Chemical Imaging Of Untreated and Alkali-treated Rice Straw supporting
confidence: 93%
“…This result was consistent with former research [59], in which the lignin distribution change in fiber cells of Eucalyptus was illustrated by Raman images with the integration of band intensity (1547-1707 cm −1 ), however, with the exception of fiber cells, other types of cells had not been studied. Furthermore, a distribution change of polysaccharides, the core components of lignocellulosic biomass transformation, had also not been studied [59]. From the histogram of lignocellulose contents of each pixel in chemical images (Fig.…”
Section: Chemical Imaging Of Untreated and Alkali-treated Rice Straw supporting
confidence: 93%
“…A higher amount of aromatic –OH groups indicates higher reactivity of lignin, while a lower amount of aliphatic –OH groups denotes a much intense pretreatment [ 45 ]. The increase in phenolic –OH content is a result of β- O -4 linkages cleavage and leads to a greater fragmentation of the lignin structure [ 46 ], as verified by the molecular weight reduction in the above results. It was also observed that the lignins from the liquid fractions of acid-catalyzed organosolv pretreatment (OS-A-S-LF and OS-A-B-LF) had the highest amount of free –OH groups (Table 4 ), which would make them the most reactive among other lignin fractions.…”
Section: Resultsmentioning
confidence: 89%
“…A large variety of depolymerization or condensation reactions typically occur within the lignin structure under such conditions. Quantitative 31 P NMR analyses of lignins isolated from various biomass pretreatment technologies have been highlighted in recent studies 101,[108][109][110][111][112][113][114][115][116][117] . As lignin has become a key genetic engineering target for the enhancement of wood quality and biofuel production 118,119 , quantitative 31 P NMR analyses also have been carried out on transgenic lignin 97,120 .…”
Section: Applications Of the 31 P Nmr Protocolmentioning
confidence: 99%